PEMBERIAN ASI EKSKLUSIF DENGAN PERKEMBANGAN BAYI USIA 6 BULAN DI WILAYAH KERJA PUSKESMAS GUNTUNG PAYUNG - Rachmadani, Zaid; Rusli, Rusdi; Agustina, Rismia (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2016)
Exclusive breasfeeding is one of several factors that influence the development of infants aged 0-6 months. Development child can be judge from the aspect of gross motor, fine motor, languageand personal social. The objective of this research was to identify relationships exclusivebreasfeeding with the development of infants aged 6 months in the working area of puskesmasGuntung Payung. The Methods of research used design cross sectional. The research wascarried out on 36 infants aged 6 months in the working area of puskesmas Guntung Payung.Instrument of research was the form of the question an interview to know the classification ofexclusive breasfeeding or not and the form of observation KPSP to assess the development ofchild. The result of this research indicated that there are 41,7% infants who are given exclusivebreastfeeding and 58,3% infants who not given exclusive breastfeeding . The development ofinfants that appropriate is 41,7%, dubious 33,3% and probably have wrong development is25,0%. The test result of chi square get p-value = 0,02. The analysis shows that there arerelationships exclusive breasfeeding with the development of infants aged 6 months in theworking area of puskesmas Guntung Payung.